PENGARUH MODEL PEMBELAJARAN DISCOVERY LEARNING TERHADAP KEMAMPUAN KOMUNIKASI MATEMATIS SISWA KELAS IX SMP N 7 PADANG - Sabrina, Fina (Departemen Matematika, 2024)
An important ability for students during the learning process is mathematical communication skills. The assessment results of grade IX students of SMPN 7 Padang show that this ability is still relatively lacking. This study examines the implementation of the Discovery Learning model making students have mathematical communication skills that are superior to the implementation of direct models. The research design uses a non-equivalent Posttest with a quasi-experimental type of research. Students who implement the Discovery Learning model have higher mathematical communication skills than the implementation of the direct model.Keywords– Model Discovery Learning, Mathematical Communication, Direct Learning